Research priorities in pediatric parenteral nutrition: a consensus and perspective from ESPGHAN/ESPEN/ESPR/CSPEN - Johnson, Mark J; Lapillonne, Alexandre; Bronsky, Jiri; Domellof, Magnus; Embleton, Nicholas; Iacobelli, Silvia; Jochum, Frank; Joosten, Koen; Kolacek, Sanja; Mihatsch, Walter A; Moltu, Sissel J; Puntis, John W L; et al. (Pediatric research, 2022)
Parenteral nutrition is used to treat children that cannot be fully fed by the enteral route. While the revised ESPGHAN/ESPEN/ESPR/CSPEN pediatric parenteral nutrition guidelines provide clear guidance on the use of parenteral nutrition in neonates, infants, and children based on current available evidence, they have helped to crystallize areas where research is lacking or more studies are needed in order to refine recommendations. This paper collates and discusses the research gaps identified by the authors of each section of the guidelines and considers each nutrient or group of nutrients in turn, together with aspects around delivery and organization. The 99 research priorities identified were then ranked in order of importance by clinicians and researchers working in the field using a survey methodology. The highest ranked priority was the need to understand the relationship between total energy intake, rapid catch-up growth, later metabolic function, and neurocognitive outcomes. Research into the optimal intakes of macronutrients needed in order to achieve optimal outcomes also featured prominently. Identifying research priorities in PN should enable research to be focussed on addressing key issues. Multicentre trials, better definition of exposure and outcome variables, and long-term metabolic and developmental follow-up will be key to achieving this. IMPACT: The recent ESPGHAN/ESPEN/ESPR/CSPEN guidelines for pediatric parenteral nutrition provided updated guidance for providing parenteral nutrition to infants and children, including recommendations for practice. However, in several areas there was a lack of evidence to guide practice, or research questions that remained unanswered. This paper summarizes the key priorities for research in pediatric parenteral nutrition, and ranks them in order of importance according to expert opinion.
Keywords: Parenteral Nutrition; Child; parenterální výživa úplná; novorozenec; Infant, Newborn; parenterální výživa; výzkum; konsensus; Research; fyziologie výživy dětí; Consensus; Humans; Infant; Child Nutritional Physiological Phenomena; lidé; kojenec; dítě; Parenteral Nutrition, Total